2017
DOI: 10.1002/adbi.201700172
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoregulation of Myofibroblast Fate and Cardiac Fibrosis

Abstract: During myocardial infarction, myocytes die and are replaced by a specialized fibrotic extracellular matrix, otherwise known as scarring. Fibrotic scarring presents a tremendous hemodynamic burden on the heart, as it creates a stiff substrate, which resists diastolic filling. Fibrotic mechanisms result in permanent scarring which often leads to hypertrophy, arrhythmias, and a rapid progression to failure. Despite the deep understanding of fibrosis in other tissues, acquired through previous investigations, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 106 publications
(161 reference statements)
0
18
0
Order By: Relevance
“…Fibroblasts are the third most common cell type in the myocardium [ 16 , 17 , 18 ]. A properly organized extracellular matrix in a physiologically healthy heart contributes to synchronized contraction, tight cell–cell coupling, and directional action potential propagation [ 55 ]. Myocardial fibrosis results from the proliferation and activation of fibroblasts and myofibroblasts, leading to excess deposition of collagenous and non-collagenous extracellular matrix [ 56 ].…”
Section: Biological Mechanisms That May Contribute To the Beneficimentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblasts are the third most common cell type in the myocardium [ 16 , 17 , 18 ]. A properly organized extracellular matrix in a physiologically healthy heart contributes to synchronized contraction, tight cell–cell coupling, and directional action potential propagation [ 55 ]. Myocardial fibrosis results from the proliferation and activation of fibroblasts and myofibroblasts, leading to excess deposition of collagenous and non-collagenous extracellular matrix [ 56 ].…”
Section: Biological Mechanisms That May Contribute To the Beneficimentioning
confidence: 99%
“…Rather, the integrated effect of HDL-targeted interventions on hard in vivo endpoints in animal models should be explored to provide stronger evidence for the potential of such therapies in terms of clinical translation. This point is, for example, illustrated by the fact that direct effects on contractility may be accompanied by indirect effects on myocardial fibrosis since mechanical cues affect myofibroblast differentiation [ 55 , 118 , 119 ]. Several recent studies in mouse models of non-ischemic heart failure have shown that HDLs may prevent heart failure development or induce reversal of existing heart failure, whereas dysfunctional HDLs may worsen heart failure development [ 59 , 120 , 121 , 122 , 123 , 124 ].…”
Section: Hdls and Heart Failure: Intervention Studies In Mouse Modmentioning
confidence: 99%
“…Furthermore, after an ischaemic insult, the formation of fibrotic scar takes place, interfering with mechanical and electrical functions of the cardiac tissue (Talman and Ruskoaho, 2016). Indeed, presence of fibrotic scar tissue leads to a reduction of the ejection fraction, due to the altered compliance of the cardiac chambers and to the increased stiffness of the myocardial matrix, thus impairing electrical properties of the heart and consequently the cardiac output (Kim P. et al, 2018). Currently, none of the commonly used therapies are able to remove such fibrotic scar, replacing the lost heart tissue with new functional cardiac cells.…”
Section: Introductionmentioning
confidence: 99%
“…The vascular endothelium, that forms the lining of all blood and lymphatic vessels, is uniquely vulnerable to the effects of chronic or intermittent hyperglycaemia[ 3 ]. Being largely dependent on glycolytic metabolism for generating adenosine triphosphate rather than oxidative phosphorylation, the uptake of glucose into endothelial cells is not downregulated as ambient glucose levels rise.…”
Section: Introductionmentioning
confidence: 99%
“…This glucotoxicity, along with the additional impacts of lipotoxicity, endoplasmic reticulum (ER) stress, inflammasome activation, oxidative and shear stress in diabetes induce pathophysiological changes in the vascular endothelium that are best characterised as “ endothel-it is ”. These changes include increased adhesion and extravasation of leucocytes, production of chemokines/cytokines, exudation of plasma, altered vasomotor tone and haemostasis, endothelial senescence and apoptosis, endothelial to mesenchymal transition (EndoMT) and neo-angiogenesis that contribute not only to accelerated atherosclerosis but also the development of progression of heart failure in diabetes[ 3 - 6 ] (Figure 1 ). Moreover, although originally considered a consequence of hypertrophy and overload, HFpEF is increasingly viewed as a “microvascular” disorder driven by endothelitis[ 7 ].…”
Section: Introductionmentioning
confidence: 99%